PERSEPSI SISWA TERHADAP KOMPETENSI KEPRIBADIAN GURU MATA PELAJARAN AGAMA ISLAM PADA SEKOLAH MENENGAH KEJURUAN (SMK) NEGERI 2 PADANG - RONI EKA PUTRA (Jurnal Bahana Manajemen Pendidikan, 2017)
This research is motivated from author's observation in SMKN 2 Padang about  the teacher's personality competence of Islamic religion .The purpose of this research is to determine the teacher's personality competence of islamic religion by aspects 1 ) acting based on norms of religious, social and cultural 2 ) presenting himself / herself as a person who is honest, noble, an example person for students and the community  3) presenting himself / herself as person who is steady, stable , wise , prudent and dignified. This research is a descriptive research. Total population in this research are  934 people . Samples were taken using stratified random sampling with 140 people. The conclusion is the teacher's personality competence in SMKN 2 padang to be improved